Planctomycetes as Novel Source of Bioactive Molecules - Graça, Ana P.; Calisto, Rita; Lage, Olga M. (Frontiers in Microbiology, 2016)
Marine environments are a fruitful source of bioactive compounds some of which are the newest leading drugs in medicinal therapeutics. Of particular importance are organisms like sponges and macroalgae and their associated microbiome. Planctomycetes, abundant in macroalgae biofilms, are promising producers of bioactive compounds since they share characteristics, like large genomes and complex life cycles, with the most bioactive bacteria, the Actinobacteria. Furthermore, genome mining revealed the presence of secondary metabolite pathway genes or clusters in 13 analyzed Planctomycetes genomes. In order to assess the antimicrobial production of a large and diverse collection of Planctomycetes isolated from macroalgae from the Portuguese coast, molecular and bioactivity assays were performed in 40 bacteria from several taxa. Two genes commonly associated with the production of bioactive compounds, nonribosomal peptide synthetases (NRPS) and polyketide synthases (PKS) genes were screened. Molecular analysis revealed that 95 % of the planctomycetes potentially have one or both secondary bioactive genes; 85 % amplified with PKS-I primers and 55 % with NRPS primers. Some of the amplified genes were confirmed to be involved in secondary metabolite pathways. Using bioinformatic tools their biosynthetic pathways were predicted. The secondary metabolite genomic potential of strains LF1, UC8 and FC18 was assessed using in silico analysis of their genomes. Aqueous and organic extracts of the Planctomycetes were evaluated for their antimicrobial activity against an environmental Escherichia coli, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Staphylococcus aureus ATCC 25923, Bacillus subtilis ATCC 6633 and a clinical isolate of Candida albicans. The screening assays showed a high number of planctomycetes with bioactive extracts revealing antifungal (43 %) and antibacterial (54 %) activity against C. albicans and B. subtilis, respectively. Bioactivity was observed in strains from Rhodopirellula lusitana, R. rubra, R. baltica, Roseimaritima ulvae and Planctomyces brasiliensis. This study confirms the bioactive capacity of Planctomycetes to produce antimicrobial compounds and encourages further studies envisaging molecule isolation and characterization for the possible discovery of new drugs.